Seed coat colour as an indicator of physiological seed quality - S. Seethaladevi; M. Kathiravan; C. Vanitha; R. Umarani; G. Preetha; S. Marimuthu; M. K. Sakthi Anand (Plant Physiology Reports, 2026)

Imaging technologies for non-invasive detection of insect pest infestations in stored food grains: a review - B. Keerthana; G. Preetha; Umapathi Krishnamoorthy; V. R. Saminathan; T. Eevera; N. Anandaraja; J. Malathi (Journal of Plant Diseases and Protection, 2026)

Acoustic detection of Callosobruchus maculatus (F.) (Coleoptera: Chrysomelidae) in green gram and cowpea using MEMS microphone system - B. Keerthana; G. Preetha; K. Umapathi; V. R. Saminathan; T. Eevera; J. Malathi; S. Santhi (Journal of Plant Diseases and Protection, 2025)

Anti-lipidemic and anti-diabetic properties of Gymnema sylvestre saponins: an in-silico approach - R. Archana Preetha; G. Dicky John Davis; M. Gowri Neelima; B. S. Chaitra; B. Kirankumar (In Silico Pharmacology, 2025)

Morphological and molecular characterization of major internal feeders in storage insect pests using SWISS- model - B. Keerthana; G. Preetha; V.R. Saminathan; M. Murugan; T. Eevera; D. Ramesh (Journal of Stored Products Research, 2025)

Usage pattern of chemicals, biologicals and veterinary medicinal products in Indian aquaculture - Prasanna K. Patil; Sudhansu S. Mishra; Pravata K. Pradhan; Sanjib K. Manna; Jawahar T. Abraham; Haresh G. Solanki; Neetu Shahi; Priyabrata Swain; Satya N. Sahoo; Satheesha Avunje; Krupesha S. R. Sharma; Rajamanickam Geetha; et al. (Reviews in Aquaculture, 2022)
The use of chemicals, biologicals and veterinary medicinal products (VMPs) helps in healthy and sustainable fish production. Information on the use of these products is essential for assessing farming practices, potential human health and environmental risks. A questionnaire‐based nationwide survey covering aquaculture farms ( n = 2936) producing carps, tilapia, pangasius and rainbow trout in freshwater and shrimp in brackishwater estimated the use of 52 different types of inputs which included disinfectants (597 g t −1 ), probiotics (2.28 kg t −1 ), environmental modifiers (22.82 kg t −1 ), nutritional supplements (1.96 kg t −1 ), natural anti‐infective agents (293 g t −1 ), herbicide and piscicides (844 g t −1 ), antibiotics (2 mg PCU −1 ), antifungal (4 mg PCU −1 ), and antiparasitic (14 mg PCU −1 ) agents. The bulk of these inputs was used for soil and water quality improvement and had low environmental and human safety concerns. The multivariate analysis revealed significant variation in the frequency and quantity of compounds use among farm groups. Redundancy analysis revealed a significant association between the number of products used and stocking density. The survey also showed a considerable influence of education and farming experience on the usage pattern of aquaculture inputs. Results of the study indicated greater reliance of farmers on the use of disinfectants for biosecurity, nutritional supplements for enhanced growth and environmental modifiers for maintaining soil and water quality in culture systems. Though there was no use of restricted antibiotics and antiparasitic agents, the development and implementation of standard regulatory guidelines are essential for safe and effective use of inputs for sustainable aquaculture.

Overfishing and Climate Drives Changes in Biology and Recruitment of the Indian Oil Sardine Sardinella longiceps in Southeastern Arabian Sea - Vasant Kripa; Kolliyil S. Mohamed; K. P. Said Koya; R. Jeyabaskaran; D. Prema; Shelton Padua; Somy Kuriakose; P. S. Anilkumar; Preetha G. Nair; T. V. Ambrose; A. M. Dhanya; K. S. Abhilash; et al. (Frontiers in Marine Science, 2018)

Report from a symposium on catalyzing primary and secondary prevention of cancer in India - Suneeta Krishnan; Preet K. Dhillon; Afsan Bhadelia; Anna Schurmann; Partha Basu; Neerja Bhatla; Praveen Birur; Rajeev Colaco; Subhojit Dey; Surbhi Grover; Harmala Gupta; Rakesh Gupta; et al. (Cancer Causes & Control, 2015)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

The impact of delayed blood centrifuging, choice of collection tube, and type of assay on 25-hydroxyvitamin D concentrations - Chu-Ling Yu; Roni T. Falk; Michael G. Kimlin; Preetha Rajaraman; Alice J. Sigurdson; Ronald L. Horst; Louis M. Cosentino; Martha S. Linet; D. Michal Freedman (Cancer Causes & Control, 2010)

Toxicity of selected insecticides to Trichogramma chilonis: Assessing their safety in the rice ecosystem - G. Preetha; J. Stanley; S. Suresh; S. Kuttalam; R. Samiyappan (Phytoparasitica, 2009)

Determination of Ultra Trace Level of Uranium in Ground Water of Different Geo-Chemical Environment by Adsorptive Stripping Voltammetry - R. K. Singhal; V. M. Joshi; J. Preetha; Rupali Karpe; Ajay Kumar; A. G. Hegde (Water, Air, & Soil Pollution, 2007)

Effect of increasing duration of diabetes mellitus type 2 on glycated hemoglobin and insulin sensitivity - Meena Verma; Sangeeta Paneri; Preetha Badi; P. G. Raman (Indian Journal of Clinical Biochemistry, 2006)

sY116, a human Y-linked polymorphic STS - G. Mustafa Saifi; Reiner Veitia; Houssein Khodjet El Khil; Sandrine Barbaux; Preetha Tilak; I. Manorama Thomas; Marc Fellous (Journal of Genetics, 2000)

A novel mutation 5’ to the HMG box of theSRY gene in a case of Swyer syndrome - G. Mustafa Saifi; Preetha Tilak; Reiner Veitia; I. Manorama Thomas; Avirachan Tharapel; Ken Mcelreavey; Mark Fellous; H. Sharat Chandra (Journal of Genetics, 1999)